C-reactive protein: structure, function, regulation, and role in clinical diseases - Zhou, Hai-Hong; Tang, Yu-Long; Xu, Tian-Hao; Cheng, Bin (Frontiers in Immunology, 2024)
Abstracts: C-reactive protein (CRP) is a plasma protein that is evolutionarily conserved, found in both vertebrates and many invertebrates. It is a member of the pentraxin superfamily, characterized by its pentameric structure and calcium-dependent binding to ligands like phosphocholine (PC). In humans and various other species, the plasma concentration of this protein is markedly elevated during inflammatory conditions, establishing it as a prototypical acute phase protein that plays a role in innate immune responses. This feature can also be used clinically to evaluate the severity of inflammation in the organism. Human CRP (huCRP) can exhibit contrasting biological functions due to conformational transitions, while CRP in various species retains conserved protective functions in vivo. The focus of this review will be on the structural traits of CRP, the regulation of its expression, activate complement, and its function in related diseases in vivo.